Obowiązek szkolny sześciolatka i jego codzienność jako wyzwanie edukacyjne — na tle reformy edukacji de lege lata i de lege ferenda - Raszewska-Skałecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The process of preparing public schools to include children at the age of 6 in the compulsory schooling system was initiated in the year 2009. The educational reform — in the field of lowering school age — from the beginning of its initiation was one of the most controversial social reforms. The lack of the acceptance of the aforementioned reform by the great majority of parents and other educational participants are results of the way in which the aforementioned reform was implemented and of the politicisation of educational solutions. This publication presents the analysis of conditions and circumstances of the shaping of the educational reform, concerning lowering educational age of children. The article was based, inter alia, on studies and opinions of the Supreme Chamber of Control and Ministry of Education in the field of preparing communes and schools to include children — at the age of 6 — in the compulsory education in the years 2009–2015.
Keywords: educational reality; educational challenge; school reform; right to education; compulsory education for a child at the age of 6; primary school; social expectations